Effects of four types of dilute acid washing on moso bamboo pyrolysis using Py–GC/MS. (June 2015) - Dong, Qing; Zhang, Shuping; Zhang, Li; Ding, Kuan; Xiong, Yuanquan
Highlights: Acid washings increased the volatile yields and the contents of phenols and sugars. HCl-washing had the most marked promotion effect on the formation of levoglucosan. Acid washings except for H2 SO4 significantly increased the methoxyeugenol yields. Abstract: The influences of four types of dilute acid washing (H2 SO4, HCl, HF, HNO3 ) on moso bamboo pyrolysis were investigated via pyrolysis–gas chromatography/mass spectrometry (Py–GC/MS). The effects of acid washings on the inorganics contents and the chemical structure were also analyzed. The results indicated that all the acid washings could effectively remove a large portion of inorganics and disrupt the chemical structure to a certain extent. HCl-washing behaved the best in removing inorganics and had the most marked disruption effect on bamboo structure. Acid washings promoted the bamboo pyrolysis and increased the contents of both phenols and sugars. HCl-washing had the most significant promotion effect on the levoglucosan formation with the absolute peak area increasing from 8.12 × 10 8 to 1.92 × 10 9 . The absolute peak areas of 2, 3-dihydrobenzofuran decreased more or less after acid washings. All the acid washings except H2 SO4 -washing could significantly increase the absolute peak area of methoxyeugenol.